UK medical students' perceptions, attitudes, and interest toward medical leadership and clinician managers - Rouhani,MJ; Burleigh,EJ; Hobbis,C; Dunford,C; Osman,NI; Gan,C; Gibbons,NB; Ahmed,HU; Miah,S (Advances in Medical Education and Practice, 2018)
Background: We aimed to determine UK medical students’ perceptions and attitudes and interest toward medical leadership and clinician managers.Methods: A cross-sectional study was conducted during the academic year 2015–2016. An online questionnaire was distributed to 2,349 final-year students from 10 UK medical schools. Participants were asked to complete a 5-point Likert scale on their current perceptions, attitudes, and interest toward medical leadership and clinician managers. They were also asked to self-rate their leadership competences set by the Medical Leadership Competency Framework and to rate the quality of management and leadership training they received from their medical school.Results: In total, we received 114 complete responses. Only 7.9% of respondents were in agreement (strongly agree or agree) when asked whether they felt they were well informed about what a managerial position in medicine entails. When asked whether clinicians should influence managerial decisions within a clinical setting, 94.7% of respondents were in agreement with the statement. About 85% of respondents were in agreement that it is important for clinicians to have managerial or leadership responsibilities, with 63.2% of students in agreement that they would have liked more management or leadership training during medical school. Over half the respondents rated their management and leadership training they received during medical school as “very poor” or “poor” (54.4%).Conclusion: Our study suggests that UK medical students have an appetite for management and leadership training and appreciate its importance but feel that the training they are receiving is poor. This suggests that there is a gap between the demand for management and leadership training and the quality of training supplied by UK medical schools.